Program Sertifikasi Guru dan Kompetensi Pedagogik GPAI - Suprapto Suprapto (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2010)
Teacher certification programs have been implemented since 2006. teacher certification aims to improve teachers professionalism, welfare, performance and inturn, sustainable education quality in Indonesia. this research results indicate, the academic qualifications of Islamic Religious Education Teachers (GPAI) SD/MI with National Standards of S1 or Diploma IV, but the pedagogic knowledge medium category. while teaching ability in planning, implementation of learning, make contact with students, and evaluationg student learning achievement has are a good.